Remote methods for research on violence against women and children: lessons and challenges from research during the COVID-19 pandemic. Issue 11 (17th November 2022) - Bhatia, Amiya; Turner, Ellen; Akim, Aggrey; Mirembe, Angel; Nakuti, Janet; Parkes, Jenny; Datzberger, Simone; Nagawa, Rehema; Kung'u, Mary; Babu, Hellen; Kabuti, Rhoda; Kimani, Joshua; et al.
Abstract : Collecting data to understand violence against women and children during and after the COVID-19 pandemic is essential to inform violence prevention and response efforts. Although researchers across fields have pivoted to remote rather than in-person data collection, remote research on violence against women, children and young people poses particular challenges. As a group of violence researchers, we reflect on our experiences across eight studies in six countries that we redesigned to include remote data collection methods. We found the following areas were crucial in fulfilling our commitments to participants, researchers, violence prevention and research ethics: (1) designing remote data collection in the context of strong research partnerships; (2) adapting data collection approaches; (3) developing additional safeguarding processes in the context of remote data collection during the pandemic; and (4) providing remote support for researchers. We discuss lessons learnt in each of these areas and across the research design and implementation process, and summarise key considerations for other researchers considering remote data collection on violence.